Magnitude and Determinant of Child Undernutrition in Southern Mali - World Vegetable Center (International Food Policy Research Institute, 2017)
This study contains data on indicators of nutritional status such as weight for height based on the framework of baseline assessments and methods developed for an agriculture technology-transfer project in southern Mali.